Sentinel Lymphonodectomy in Early Vulvar Cancer in Daily Practice: a Multicenter Experience from Germany Sentinel-Lymphonodektomie bei Vulvakrebs im Frühstadium in der täglichen Praxis: eine multizentrische Erfahrung aus Deutschland - Soergel, Philipp; Hempel, Matthias; Gallwas, Julia; Dannecker, Christian; Woelber, Linn; Klapdor, Ruediger; Hantschmann, Peer; Forner, Dirk M.; Gaß, Paul; Hampl, Monika (Geburtshilfe und Frauenheilkunde, 2025)
Objective Inguinal sentinel lymph node dissection has been shown to be safe in early vulvar cancer in several studies and is considered or even recommended in many guidelines. The prognosis of inguinal recurrence is often poor and associated with significant mortality. To ensure an acceptably low false-negative rate and recurrence, vulvar sentinel lymph node dissection should only be performed using high-quality standards. This retrospective study aims to investigate the incidence of isolated groin recurrence in daily practice in six large cancer centers in Germany. Methods We identified all patients with early vulvar cancer in 2009-2015 who underwent inguinal sentinel lymphonodectomy and presented with node-negative final histologic results. Patient details regarding disease stage, sentinel procedure, and follow-up were examined using local cancer databases and patient registries. Results A total of 414 patients with available follow-up data were found, with a mean follow-up time of 38.4 months. The mean tumor size, measured in the dermal plane before surgery, was 40.0mm, with a median tumor size of 36mm. Isolated groin recurrence was found in 13 of 414 cases, leading to an isolated groin recurrence rate of 3.1%. The mean time to isolated groin recurrence was 17.7 months. There was no statistically significant association of any of the different quality requirements (tumor size <4cm, unifocal tumor, histologic ultra-staging, and preoperative exclusion of suspicious groins) with isolated groin recurrence. Conclusion Sentinel lymphadenectomy in vulvar cancer is a safe procedure in daily practice. The requirements of the cancer guidelines (unifocal tumor, ≤4cm, histologic ultrastaging, and exclusion of suspicious groins preoperatively) should be followed to ensure a low isolated groin recurrence rate. However, in this study, we could not find any difference between the patients who fulfilled the guideline requirements and those who did not.
CRIS-Team Scopus Importer:2025-04-11
Keywords: groin; sentinel; vulva; vulvar cancer